Reactive Oxygen Species and Nitric Oxide in Cutaneous Leishmaniasis - Maria Fátima Horta; Bárbara Pinheiro Mendes; Eric Henrique Roma; Fátima Soares Motta Noronha; Juan Pereira Macêdo; Luciana Souza Oliveira; Myrian Morato Duarte; Leda Quercia Vieira (Journal of Parasitology Research)
Cutaneous leishmaniasis affects millions of people around the world. Several species of Leishmania infect mouse strains, and murine models closely reproduce the cutaneous lesions caused by the parasite in humans. Mouse models have enabled studies on the pathogenesis and effector mechanisms of host resistance to infection. Here, we review the role of nitric oxide (NO), reactive oxygen species (ROS), and peroxynitrite (ONOO−) in the control of parasites by macrophages, which are both the host cells and the effector cells. We also discuss the role of neutrophil-derived oxygen and nitrogen reactive species during infection with Leishmania. We emphasize the role of these cells in the outcome of leishmaniasis early after infection, before the adaptive Th-cell immune response.